SCIENTIFIC PRODUCTION ON THE CLAY MINERAL ILLITE: A BIBLIOMETRIC STUDY - da Silva, Ênio Vieira Alves; Lima, Ezequiel da Cruz; Alves, Sandra Maria Borges Costa; Sobrinho, Naiara de Oliveira; Barros e Silva, Teresa Maria; de Sousa, Antonio Aurélio Barbosa; Queiroz, Ujehny Aparecida Santos; Ribeiro, Aurilene Braga (Seven Editora, 2025)
Clays have been present in society since the beginning of civilization, playing an important role in the early development of man. From the moment that man began to acquire knowledge about the material, in which it served him, he began to analyze its behavior and its application. However, he needed to know the raw material and that there was a difference between them in terms of the structural composition of each clay. Therefore, the objective of this work is the bibliometric survey on the illite clay mineral. The methodology was the study of art and was based on the Web of Science survey, with a time interval of 10 years (2011-2022). Within the base of the Web of Science, filters were applied for search refinement, and the term illita was inserted in the English language. Also, in addition to the year, authors with more publications and the main categories of the database were searched. After processing the data, author Zwingmann was the author with the most publications, followed by Hong and soon after Clauer, each with 29, 27 and 26, respectively. The category with the most publications was Geosciences Multidisciplinary, Geochemistry Geophysics and Mineralogy. DOI: https://doi.org/10.56238/sevened2025.036-030